Anisotropic flow in Xe-Xe collisions at √sNN=5.44 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; et al. (Physics letters, 2018)
The first measurements of anisotropic flow coefficients vn for mid-rapidity charged particles in Xe-Xe collisions at sNN=5.44 TeV are presented. Comparing these measurements to those from Pb-Pb collisions at sNN=5.02 TeV, v2 is found to be suppressed for mid-central collisions at the same centrality, and enhanced for central collisions. The values of v3 are generally larger in Xe-Xe than in Pb-Pb at a given centrality. These observations are consistent with expectations from hydrodynamic predictions. When both v2 and v3 are divided by their corresponding eccentricities for a variety of initial state models, they generally scale with transverse density when comparing Xe-Xe and Pb-Pb, with some deviations observed in central Xe-Xe and Pb-Pb collisions. These results assist in placing strong constraints on both the initial state geometry and medium response for relativistic heavy-ion collisions.